Tirona ancestral house a descriptive study on the transformation and preservation strategies in a 19th century historical home interior in Imus City, Cavite - Mercado, Catherine Anne M.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
The study operationalized a qualitative approach to reading the meanings and motives behind the transformations and preservation startegies used in the interiors of the Tirona ancestral house. Using purposive sampling, the parameters were set as follows a) built in the 19th century b) located within Imus City, Cavite c) officially declared as a historical house and d) privately owned. The research involved an inspection and documentation of each rooms, followed by desk research and interviews with key informants, and lastly, interpretation of the data gathered through content analysis. Each room was documented using the observation guide and recording devices such as a phone, tablet, and camera. Due to lack of available public records, a reconstruction of the interiors' transformations was carried out based on the oral narratives of the key informants and other secondary sources. Findings revealed that the transformation of the interiors was motivated by a desire to maintain status, to control the environment, and to satisfy new requirements of comfort, privacy, and security. Special emphasis was given to the historic preservation of the building shell, while some of the interior spaces were repurposed, removed, or modernized. Furthermore, results pointed out the need for an interior design perspective in protecting our collective heritage. Trained in space planning and understanding space, interior designers may take part in the preservation and restoration of historical interiors.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Historic buildings -- Conservation and restoration -- Philippines -- Imus City (Cavite).; Interior architecture -- Conservation and restoration -- Philippines -- Imus City (Cavite).